Pengaruh E-Service Quality Terhadap Kepuasan Wisatawan Nusantara di AiryRooms Kecamatan Kuta Bali - Yofana Virgianne; Ni Made Ariani; Fanny Maharani Suarka (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2019)
In digital era nowadays, the quality of electronic services needs to be managed appropriately. According to Tjiptono (2012), when quality managed properly, it contributes positively to the customer satisfaction and loyalty. This study aims to determine the influence of e-service quality towards customer satisfaction of AiryRooms Kuta. Data analysis techniques used descriptive statistics to describe the tourist characteristics, Likert scale analysis to describe the e-service quality and customer satisfaction. Inferential statistics such as validity test, reliability test, normality test, simple regression test, coefficient of determination test, and t test describe the influence of e-service quality towards customer satisfaction. The results showed that AiryRooms Kuta consumers were dominated by women aged 21 to 30 years who were unmarried with income of under one million rupiah, his worked as a student/ college student, came from Jakarta, dominated by consumers who organize their own trips for recreation/ vacation, travel with friends using airplanes, travel on weekdays, stayed at Airy Kuta District for 1 until 3 nights, got information about Airy through online media and frequency of used Airy for one year are 1 until 5 times. The results also showed that AiryRooms has a good e-service quality and consumer is satisfied to stay in AiryRooms Kuta District. E-service quality has a positive and significant influence on customer satisfaction. E-Service Quality has an influence of 47.6% on customer satisfaction. The suggestion for AiryRooms is to repair their refund system, improve their product quality, service quality, brand image so that consumers want to repurchase.